Clinical presentation, management, and research progress of adrenal schwannoma - Xu, Shenghan; Yu, Ying; Zhang, Yajuan; Wen, Yong; Li, Wei; Huang, Tao; Che, Bangwei; Zhang, Wenjun; Zhang, Jinjuan; Tang, Kaifa (Frontiers in Surgery, 2022)
Objective: This study shares our experience in the management of Adrenal schwannoma (AS). Methods: The clinical data of 8 patients with AS in our hospital from April 2007 to April 2022 were analyzed retrospectively. Results: A total of 1309 patients with adrenal lesions were treated in the affiliated hospital of Guizhou Medical University for 15 years, of which only 8 cases were diagnosed as AS, accounting for 0.61%. Among the 8 patients with AS, there were 5 females and 3 males, with an average age of 48.63±12.05 years, and the average maximum diameter of the tumor was 6.96±1.83 cm. All patients underwent adrenalectomy and were pathologically diagnosed as AS after the operation. The average follow-up time of 8 patients with AS was 60.13±22.33 months, and there was no recurrence or metastasis. Conclusion: The retroperitoneum is an uncommon site for schwannoma tumors, and among adrenal incidentalomas, the schwannoma is rare. The disease lacks specific clinical and imaging features, but correct diagnosis before the pathological examination is very important for clinical management and surgical decision. When imaging examination indicates a slow-growing retroperitoneal mass, schwannoma should be considered. Surgical resection is the main treatment. Pathology is the gold standard for diagnosis. Most of the tumors are benign and have a good prognosis. There is a risk of recurrence after the operation, and it should be followed up actively.